Preparation method and application of carbon material loaded ruthenium nanocrystal

Through the preparation method of uniformly growing ruthenium nanocrystals on carbon materials, the problem of insufficient catalytic performance of carbon-supported ruthenium nanocrystals in the prior art is solved, and high catalytic activity and electrochemical performance are improved, suitable for a variety of energy and catalysis field.

CN119303569AInactive Publication Date: 2025-01-14YEAL ELECTRIC CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411423176.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The lack of effective preparation methods for carbon-supported ruthenium nanocrystals in the prior art limits its application in the fields of catalysis, electronics and energy, especially the improvement of catalytic and electrochemical properties.

Method used

By stirring the ruthenium metal salt and acid under specific conditions, adding carbon material to form a suspension, and reacting in an oil bath pot, high-purity carbon-supported ruthenium nanocrystals are obtained, and then cooling, cleaning and drying is performed to achieve ruthenium nanocrystals. The uniform growth and controllable morphology.

Benefits of technology

The high catalytic activity, selectivity and stability of carbon-supported ruthenium nanocrystals have been achieved, which significantly improves its performance in electrocatalytic reactions. It is suitable for applications such as supercapacitors, lithium-air batteries and fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119303569A_ABST
    Figure CN119303569A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a carbon material loaded ruthenium nanocrystal, and belongs to the technical field of material chemistry. Comprising the following steps: adding a carbon material into an ethylene glycol solution containing ruthenium metal salt, adding a proper amount of acid, and reacting in a temperature interval of 25-180 DEG C to obtain the carbon-loaded ruthenium nanocrystal. The method provided by the invention is simple, easy to operate and low in cost, the ruthenium nanocrystals can be uniformly dispersed on the surface of the carbon material by using conventional equipment, the method is suitable for industrial production, and the prepared ruthenium / carbon material has ultrahigh catalytic activity, catalytic selectivity and catalytic stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material chemistry, and in particular relates to a preparation method and application of carbon material loaded ruthenium nanocrystals. Background Art

[0002] Carbon materials are divided into two types: crystalline carbon and amorphous carbon due to their different structures. They have excellent electrical conductivity and electron mobility, excellent high temperature resistance, good mechanical properties and chemical stability. Carbon materials have special electronic structure properties and excellent semiconductor properties close to silicon, and have great application potential in catalysis, electronic devices, semiconductors and energy storage. However, similar to other carbon materials, the catalytic performance of pure carbon materials is not very high.

[0003] The controllable preparation of carbon-supported ruthenium nanocrystal catalysts effectively regulates the charge transfer ability of carbon materials and ruthenium nanocrystals. In carbon-supported ruthenium nanocrystal catalysts, ruthenium nanocrystals grow evenly on the surface of carbon materials, significantly increasing the number of active sites and catalytic active area of ​​the catalyst, and significantly improving the catalytic activity, selectivity and stability of the catalyst.

[0004] Currently, carbon-supported metal oxides are widely studied, and have been shown to have high catalytic activity. However, there are still no reports on the preparation method of carbon-supported ruthenium nanocrystals.

[0005] Therefore, the field urgently needs to develop a method for carbon-loaded ruthenium nanocrystals that is simple, easy to operate, green and environmentally friendly, requires conventional equipment, and is easy to industrialize, so as to significantly improve the electrochemical properties of the material, which is of great significance in the fields of catalysis, electronics, energy, etc. Summary of the invention

[0006] The purpose of the present invention is to provide a preparation method and application of carbon material loaded ruthenium nanocrystals to solve the technical problems mentioned in the above background technology.

[0007] To achieve the above-mentioned purpose, the specific technical scheme of the preparation method and application of a carbon material-supported ruthenium nanocrystal of the present invention is as follows:

[0008] A method for preparing carbon material-loaded ruthenium nanocrystals comprises the following steps:

[0009] Step S1: adding an appropriate amount of ruthenium metal salt and acid into a round-bottom flask, and vigorously stirring at 25-180° C. to obtain a homogeneous solution;

[0010] Step S2: adding an appropriate amount of carbon material to the solution of step S1, and stirring at room temperature to obtain a suspension of carbon material loaded with metal salt;

[0011] Step S3: placing the solution obtained in step S2 in an oil bath to react and obtain carbon-supported ruthenium nanocrystals;

[0012] Step S4: Cool, wash and dry the carbon material-supported ruthenium nanocrystals obtained in step S3 to obtain high-purity carbon-supported ruthenium nanocrystals.

[0013] Furthermore, the carbon material in step S2 includes one or a combination of two or more of graphite carbon, fullerene, carbon nanotube, graphene, graphyne and graphyne.

[0014] Further, the ruthenium metal salt in step S1 includes one or a combination of two or more of ruthenium chloride hydrate, ruthenium bromide, ruthenium acetylacetonate and ruthenium iodide;

[0015] Calculated as ruthenium element, the concentration of ruthenium ions in the ruthenium metal salt is 0.01 to 50 g / L.

[0016] Furthermore, the acid in step S1 includes at least one of hydrochloric acid, formic acid, ascorbic acid, sodium citrate and glucose.

[0017] Furthermore, in the suspension in step S2, the mass ratio of the compound containing ruthenium element to the carbon material is 0.01-50; preferably 1-20.

[0018] Furthermore, the concentration of the ruthenium metal salt in step S1 is 0.01 to 100 g / L, preferably 20 g / L.

[0019] Furthermore, the reaction temperature of step S2 is 25-180°C and the reaction time is 0.5-12h; preferably, the reaction temperature is 80-150°C and the reaction time is 1-5h;

[0020] The cooling temperature of step S3 is -60 to 30°C; preferably 0 to 25°C;

[0021] The step S3 is performed by washing with pure water or ethanol.

[0022] The present invention also provides a carbon material-supported ruthenium nanocrystal catalyst, and the carbon material-supported ruthenium nanocrystal catalyst is prepared by the above method;

[0023] The ruthenium nanocrystals of the carbon material-loaded ruthenium nanocrystal catalyst grow uniformly on the surface of the carbon material, and their morphology and size are controllable.

[0024] The present invention also provides an application of a carbon material-supported ruthenium nanocrystal catalyst, wherein the carbon material-supported ruthenium nanocrystal catalyst is used as an electrocatalytic hydrogen evolution reaction catalyst, an electrocatalytic oxygen evolution reaction catalyst, an electrocatalytic oxygen reduction reaction catalyst, an electrocatalytic carbon dioxide reduction reaction catalyst, an electrocatalytic nitrogen reduction reaction catalyst, a supercapacitor, a lithium-air battery, a lithium-sulfur battery or a fuel cell.

[0025] In the solution described in step S1 of the present invention, the mass ratio of ruthenium metal salt to carbon material is 0.01-50, for example, 0.1:1, 1:1, 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, 50:1, etc., preferably 1-20.

[0026] The concentration of the carbon material in step S2 of the present invention is 0.01 to 100 g / L, for example, 0.01 g / L, 0.1 g / L, 1 g / L, 5 g / L, 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L, 50 g / L, 55 g / L, 60 g / L, 60 g / L, 70 g / L, 75 g / L, 80 g / L, 85 g / L, 90 g / L, 95 g / L, 100 g / L, etc., preferably 20 g / L.

[0027] Calculated in terms of ruthenium element, the concentration of the ruthenium metal salt solution is 0.01 to 50 g / L, for example, 0.01 g / L, 1 g / L, 5 g / L, 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L, 50 g / L, etc.

[0028] The reaction temperature of step S2 of the present invention is 25-180°C, for example, 25°C, 35°C, 45°C, 55°C, 65°C, 75°C, 85°C, 95°C, 105°C, 115°C, 125°C, 135°C, 145°C, 155°C, 165°C, 175°C, etc., and the reaction time is 0.5-12h, for example, 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, etc.; preferably, the reaction temperature is 80-150°C, and the reaction time is 1-5h.

[0029] The cooling temperature described in step S4 of the present invention is -60 to 30°C, for example, -45°C, -30°C, -18°C, 0°C, 10°C, 15°C, 22°C, 25°C, 28°C, etc.; preferably 0 to 25°C.

[0030] The preparation method and application of a carbon material-loaded ruthenium nanocrystal of the present invention have the following advantages:

[0031] The preparation method provided by the invention has ingenious design idea, simple process, easy operation, conventional equipment, is green and environmentally friendly, and is convenient for industrial production.

[0032] The carbon-supported ruthenium nanocrystals prepared by the present invention have an ultra-large specific surface area, high electrical conductivity, and ultra-high catalytic activity, and are successfully used as catalysts for electrocatalytic hydrogen evolution (oxygen evolution, oxygen reduction, carbon dioxide reduction, nitrogen reduction) reactions, supercapacitors, lithium-air batteries, lithium-sulfur batteries, fuel cell lithium battery negative electrode materials, supercapacitors, lithium-air (sulfur) batteries, and fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Scanning electron microscope images of carbon-supported ruthenium nanocrystals prepared in Example 2 ((a) low-magnification and (b) high-magnification scanning electron microscope images of carbon-supported ruthenium nanocrystals).

[0034] Figure 2 Transmission electron microscopy images of carbon-supported ruthenium nanocrystals prepared in Example 2 (transmission electron microscopy image (TEM) and high-resolution transmission electron microscopy image (HRTEM); (a) low-magnification and (b) transmission electron microscopy images of carbon-supported ruthenium nanocrystals; (c) low-magnification and (d) high-resolution transmission electron microscopy images).

[0035] Figure 3 The XPS spectra of carbon-supported ruthenium nanocrystals prepared in Example 2 (X-ray photoelectron spectrum of carbon-supported ruthenium nanocrystals. X-ray photoelectron spectrum of carbon materials (a) full spectrum and (b) C1s spectrum. Carbon-supported ruthenium nanocrystals (c) Ru Carbon-supported ruthenium nanocrystals (c) full spectrum and (d) Ru 3d+C 1s spectrum.

[0036] Figure 4 The catalytic performance test of the carbon-supported ruthenium nanocrystals prepared in Example 2 ((a) linear polarization curve, (b) Tafel curve, (c) overpotential values ​​at different current densities, (d) impedance test curve, (e) relationship between current density and potential at different scanning rates, (f) relationship between scanning rate and current density, (g) schematic diagram of the test stack, (h) relationship between current density and time). DETAILED DESCRIPTION

[0037] In order to better understand the purpose, structure and function of the present invention, the preparation method and application of carbon material-loaded ruthenium nanocrystals of the present invention are further described in detail below in conjunction with the accompanying drawings.

[0038] Embodiment 1:

[0039] A method for preparing carbon material-loaded ruthenium nanocrystals comprises the following steps:

[0040] (1) adding 5 g of the carbon material to an ethylene glycol solution (500 mL) containing 2 g of ruthenium chloride and 1 g of glucose, and mixing them uniformly to obtain a suspension; the mass ratio of ruthenium chloride to the carbon material in the suspension is 1:2.5;

[0041] (2) reacting the suspension obtained in step (1) at 120° C. for 12 h to obtain an intermediate product of carbon-supported ruthenium nanocrystals;

[0042] (3) The intermediate product of carbon-supported ruthenium nanocrystals obtained in step (2) is cooled to 25° C., washed with ultrapure water and ethanol, and dried to obtain the final product of carbon-supported ruthenium nanocrystals.

[0043] The carbon-supported ruthenium provided in Example 1 can be used as a catalyst.

[0044] Embodiment 2:

[0045] A method for preparing carbon-supported ruthenium nanocrystals comprises the following steps:

[0046] (1) adding 20 mg of carbon cloth to an ethylene glycol solution (10 mL) containing 20 mg of ruthenium chloride and 10 mg of glucose, and mixing them evenly to obtain a suspension; the mass ratio of ruthenium chloride to carbon material in the suspension is 1:1;

[0047] (2) reacting the suspension obtained in step (1) at 180° C. for 12 h to obtain an intermediate product of carbon-supported ruthenium nanocrystals;

[0048] (3) The intermediate product of carbon-supported ruthenium nanocrystals obtained in step (2) is cooled to 25° C., washed with ultrapure water and ethanol, and dried to obtain the final product of carbon-supported ruthenium nanocrystals.

[0049] The carbon-supported ruthenium nanocrystals obtained in Example 2 were characterized by scanning electron microscopy (SEM). Figure 1 The scanning electron microscope image of the carbon-supported ruthenium nanocrystals obtained in Example 2 is shown in FIG. Figure 1 In both a and 1b, white granular nanocrystals can be seen to be independently distributed on the surface of the carbon material;

[0050] The carbon-supported ruthenium nanocrystals obtained in Example 2 were characterized by transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM). Figure 2 TEM image ( Figure 2 a-2c) and HRTEM images ( Figure 2 d) From the characterization results, it can be further confirmed that the ruthenium nanocrystals are independently dispersed on the surface of the carbon material, and the ruthenium nanocrystals have a 0.21 nm interplanar spacing;

[0051] The carbon-supported ruthenium nanocrystals obtained in Example 2 were subjected to X-ray photoelectron spectroscopy (XPS) analysis on an ESCALab 250Xi X-ray photoelectron spectrometer. Figure 3 The XPS spectrum is the full spectrum of the X-ray photoelectron spectrum of carbon materials ( Figure 3 a) and high-resolution C1s spectra ( Figure 3 b) can confirm the successful synthesis of carbon materials; from the full spectrum of X-ray photoelectron spectroscopy of carbon-supported ruthenium nanocrystals ( Figure 3 c) and Ru 3d+C 1s spectra ( Figure 3 d) The successful synthesis of carbon-supported ruthenium nanocrystal catalyst can be confirmed.

[0052] The electrochemical performance of the carbon-supported ruthenium nanocrystals obtained in Example 2 was tested. Figure 4 The catalytic performance test results are shown in Table 4. From the linear polarization curve (4a) and the overpotential values ​​at different current densities ( Figure 4 c) The current density can be confirmed to be 100 mA cm -2 The required overpotential is less than 30mV and the current density is 800mA cm -2 The overpotential required is less than 120mV, and the performance of carbon-supported ruthenium nanocrystals in water electrolysis and hydrogen evolution is much higher than that of commercial Pt / C. The Tafel slope test results further show that the catalyst has a catalytic performance that exceeds that of commercial Pt / C. Electrochemical impedance test ( Figure 4 d) The results show that the prepared carbon-supported ruthenium nanocrystals have excellent electrical conductivity; the electrochemical active area test ( Figure 4 e and 4f) results show that carbon-supported ruthenium nanocrystals have a large electrochemical active area; based on the prepared carbon-supported ruthenium nanocrystals assembled into a small battery stack ( Figure 4 g), stability test ( Figure 4 g) shows excellent stability. The carbon-supported ruthenium nanocrystals obtained in Example 2 can be used as a hydrogen evolution catalyst.

[0053] Embodiment 3:

[0054] A method for preparing carbon-supported ruthenium nanocrystals comprises the following steps:

[0055] (1) adding 40 mg of carbon cloth to an ethylene glycol solution (10 mL) containing 20 mg of ruthenium chloride and 10 mg of sodium citrate, and mixing them evenly to obtain a suspension; the mass ratio of ruthenium chloride to carbon material in the suspension is 1:2;

[0056] (2) reacting the suspension obtained in step (1) at 150° C. for 5 h to obtain an intermediate product of carbon-supported ruthenium nanocrystals;

[0057] (3) The intermediate product of carbon-supported ruthenium nanocrystals obtained in step (2) is cooled to 25° C., washed with ultrapure water and ethanol, and dried to obtain the final product of carbon-supported ruthenium nanocrystals.

[0058] The carbon-supported ruthenium nanocrystals obtained in Example 3 can be used for electrocatalytic carbon dioxide reduction reaction.

[0059] Embodiment 4:

[0060] A method for preparing carbon-supported ruthenium nanocrystals comprises the following steps:

[0061] (1) adding 60 mg of carbon cloth to an ethylene glycol solution (10 mL) containing 20 mg of ruthenium chloride and 10 mg of ascorbic acid, and mixing them uniformly to obtain a suspension; the mass ratio of ruthenium chloride to carbon material in the suspension is 1:3;

[0062] (2) reacting the suspension obtained in step (1) at 180° C. for 5 h to obtain an intermediate product of carbon-supported ruthenium nanocrystals;

[0063] (3) The intermediate product of carbon-supported ruthenium nanocrystals obtained in step (2) is cooled to 25° C., washed with ultrapure water and ethanol, and dried to obtain the final product of carbon-supported ruthenium nanocrystals.

[0064] The carbon-supported ruthenium nanocrystals obtained in Example 4 can be used as a fuel cell.

[0065] Embodiment 5:

[0066] A method for preparing carbon-supported ruthenium comprises the following steps:

[0067] (1) adding 100 mg of carbon cloth to an ethylene glycol solution (10 mL) containing 20 mg of ruthenium chloride and 10 mg of ascorbic acid, and mixing them uniformly to obtain a suspension; the mass ratio of ruthenium chloride to carbon material in the suspension is 1:5;

[0068] (2) reacting the suspension obtained in step (1) at 180° C. for 2 h to obtain a carbon-supported ruthenium intermediate product;

[0069] (3) The carbon-supported ruthenium intermediate product obtained in step (2) is cooled to 25° C., washed with ultrapure water and ethanol, and dried to obtain the carbon-supported ruthenium final product.

[0070] The carbon-loaded ruthenium material prepared in Example 5 selectively adsorbs organic matter and can be used for sewage treatment.

[0071] Embodiment 6:

[0072] A method for preparing an iodine-doped graphene material comprises the following steps:

[0073] (1) adding 100 mg of carbon cloth to an ethylene glycol solution (10 mL) containing 50 mg of ruthenium chloride and 10 mg of ascorbic acid, and mixing them uniformly to obtain a suspension; the mass ratio of ruthenium chloride to carbon material in the suspension is 1:2;

[0074] (2) reacting the suspension obtained in step (1) at 180° C. for 8 h to obtain a carbon-supported ruthenium intermediate product;

[0075] (3) The carbon-supported ruthenium intermediate product obtained in step (2) is cooled to 25° C., washed with ultrapure water and ethanol, and dried to obtain the carbon-supported ruthenium final product.

[0076] The carbon-supported ruthenium nanocrystals prepared in Example 6 can be used in zinc-air batteries.

[0077] It is to be understood that the present invention is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application are within the scope of protection of the present invention.

Claims

1. A method for preparing carbon material-supported ruthenium nanocrystals, characterized in that: The specific steps include: Step S1: Add appropriate amounts of ruthenium metal salt and acid into a round-bottom flask, and vigorously stir at 25-180° C. to obtain a homogeneous solution; Step S2: adding an appropriate amount of carbon material to the solution of step S1, and stirring at room temperature to obtain a suspension of carbon material loaded with metal salt; Step S3: placing the solution obtained in step S2 in an oil bath to react and obtain carbon-supported ruthenium nanocrystals; Step S4: Cool, wash and dry the carbon material-supported ruthenium nanocrystals obtained in step S3 to obtain high-purity carbon-supported ruthenium nanocrystals.

2. The method for preparing carbon material-supported ruthenium nanocrystals according to claim 1, characterized in that: The carbon material in step S2 includes one or a combination of two or more of graphite carbon, fullerene, carbon nanotube, graphene, graphyne and graphyne.

3. The method for preparing carbon material-supported ruthenium nanocrystals according to claim 1, characterized in that: The ruthenium metal salt in step S1 includes one or a combination of two or more of ruthenium chloride hydrate, ruthenium bromide, ruthenium acetylacetonate and ruthenium iodide; Calculated as ruthenium element, the concentration of ruthenium ions in the ruthenium metal salt is 0.01 to 50 g / L.

4. The method for preparing carbon material-supported ruthenium nanocrystals according to claim 1, characterized in that: The acid in step S1 includes at least one of hydrochloric acid, formic acid, ascorbic acid, sodium citrate and glucose.

5. The method for preparing carbon material-supported ruthenium nanocrystals according to claim 1, characterized in that: In the suspension in step S2, the mass ratio of the compound containing ruthenium element to the carbon material is 0.01-50, preferably 1-20.

6. The method for preparing carbon material-supported ruthenium nanocrystals according to claim 1, characterized in that: The concentration of the ruthenium metal salt in step S1 is 0.01-100 g / L, preferably 20 g / L.

7. The method for preparing carbon material-supported ruthenium nanocrystals according to claim 1, characterized in that: The reaction temperature of step S2 is 25-180°C and the reaction time is 0.5-12h; preferably the reaction temperature is 80-150°C and the reaction time is 1-5h; The cooling temperature of step S3 is -60 to 30°C; preferably 0 to 25°C; The step S3 is performed by washing with pure water or ethanol.

8. A carbon material supported ruthenium nanocrystal catalyst, characterized in that: The carbon material-supported ruthenium nanocrystal catalyst is prepared by the method of any one of claims 1 to 7; The ruthenium nanocrystals of the carbon material-loaded ruthenium nanocrystal catalyst grow uniformly on the surface of the carbon material, and their morphology and size are controllable.

9. An application of a carbon material-supported ruthenium nanocrystal catalyst, characterized in that: The carbon material-supported ruthenium nanocrystal catalyst is used as an electrocatalytic hydrogen evolution reaction catalyst, an electrocatalytic oxygen evolution reaction catalyst, an electrocatalytic oxygen reduction reaction catalyst, an electrocatalytic carbon dioxide reduction reaction catalyst, an electrocatalytic nitrogen reduction reaction catalyst, a supercapacitor, a lithium-air battery, a lithium-sulfur battery or a fuel cell.

Citation Information

Cited By

  • Acetylene-enriched carbon-ruthenium catalyst as well as preparation method and application thereof

    CN121198289A

  • Acetylene-rich carbon-ruthenium nickel alloy catalyst as well as preparation method and application thereof

    CN121222442A